2018
DOI: 10.3390/v10060315
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization and Phylogenetic Analysis of Small Ruminant Lentiviruses Detected in Spanish Assaf Sheep with Different Mammary Lesions

Abstract: Small Ruminant Lentiviruses (SRLVs) are widespread in many countries and cause economically relevant, slow, and persistent diseases in sheep and goats. Monitoring the genetic diversity of SRLVs is useful to improve the diagnostic tools used in the eradication programs. In this study, SRLVs detected in Spanish Assaf sheep with different grades of lymphoproliferative mastitis were sequenced. Genetic characterization showed that most samples belonged to type A and were closer to Spanish SRLV isolates previously c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
3
8
0
3
Order By: Relevance
“…The analysis of Polish LTR sequences revealed that sequences corresponding to the TATA box, AP-4, AML-vis, and polyadenylation signal (poly A) were quite conserved which was previously reported in strains from different geographic areas. This sequence conservation argues in favor of their importance in the replication strategies of SRLVs [12,26,42,[68][69][70]. On the other hand, considerable alteration was observed in AP-1 sites, which confirmed previous findings suggesting that AP-1 sites may by functional even despite some changes [70,71].…”
Section: Discussionsupporting
confidence: 87%
“…The analysis of Polish LTR sequences revealed that sequences corresponding to the TATA box, AP-4, AML-vis, and polyadenylation signal (poly A) were quite conserved which was previously reported in strains from different geographic areas. This sequence conservation argues in favor of their importance in the replication strategies of SRLVs [12,26,42,[68][69][70]. On the other hand, considerable alteration was observed in AP-1 sites, which confirmed previous findings suggesting that AP-1 sites may by functional even despite some changes [70,71].…”
Section: Discussionsupporting
confidence: 87%
“…The sequence analysis shows that the TATA box and the poly (A) site were highly conserved, it is necessary for the virus to maintain these chains of genetic mutations (Mendiola et al, 2019), but the other parties of the LTR may have more mutations (Gayo et al, 2018). Indeed, the regulatory sequences of the genome correspond to non-coding sequences involved in the different stages of the retroviral cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Die Beschreibung von Euterveränderungen bei einer Vielzahl verschiedener Schafrassen spricht nicht für eine rassebedingt bevorzugte Manifestation der Erkrankung im Euter [9-11, 24, 27, 30]. Auch die genetische Charakterisierung von MVV aus dem Eutergewebe infizierter Schafe ergab keinen Hinweis auf MVV-Varianten mit einem besonderen Tropismus für die Milchdrüse [39]. Dennoch ist bemerkenswert, dass in einer hochgradig durchseuchten Herde ( > 90 % seropositive Mutterschafe) bei keinem Tier Lungen-oder ZNS-Symptome auftraten und das MVV-Infektionsgeschehen sich nur als indurative Mastitis manifestierte.…”
Section: Diskussionunclassified